The influence of drought stress on growth, yield, and yield components of some maize genotypes - Kamara, A.Y.; Menkir, A.; Badu-Apraku, Baffour; Ibikunle, O. (Cambridge University Press, 2003)
The risk of drought is high in the Sudan savannah zone of West and Central Africa because rainfall in this area is unpredictable in quantity and distribution. Thus, improved maize genotypes tolerant to drought could stabilize maize grain yield in this zone, where recurrent drought threatens grain production. Six maize genotypes, two each of hybrids, open-pollinated varieties (OPVs) and landraces, were evaluated for tolerance to terminal water deficit before flowering. Water deficit significantly reduced growth, grain yield and yield components of the maize genotypes. Significant differences were observed among genotypes for all the traits measured. One hybrid, 9011-30, and two improved OPVs, STR-EV-IWD and IYFD-C0, that showed tolerance to water stress recorded higher grain yield, and accumulated and partitioned more assimilates to the grain than the drought-susceptible genotypes. Also the drought-tolerant genotypes, 9011-30, STR-EV-IWD and IYFD-C0 had more ears/plant and greater numbers of kernels/ear. These genotypes could serve as sources of drought tolerance for the development and improvement of new drought-tolerant maize genotypes.